Analysis of Moral Values In Walt Disney Pictures and Pixar Animation Studios' Luca - Vanda Kristanti; Ira Maisarah (Journal of English for Specific Purposes in Indonesia (JESPI), 2023)
This research discusses the analysis of moral values in the animated show "Luca". The purpose of this study was to find out the moral value contained in the animated show "Luca" Produced by Walt Disney Pictures and Pixar Animation Studios. This research was carried out based on a qualitative approach that resulted in descriptive using the semiotic approach of Roland Barthes's theory. The data sources used in this study are primary data sources and secondary data sources. Data collection techniques through documentation to find research data through scenes (film scripts, images, or films) from the animated film Luca. The results of this research in Luca animation are wise, patience, never giving up, honesty, discipline, helpfulness, democratic, cooperation, courage and kindness.